Knowledge, attitudes, and practices on camel respiratory diseases and conditions in Garissa and Isiolo, Kenya - Othieno, Joseph; Njagi, Obadiah; Masika, Sophie; Apamaku, Michael; Tenge, Evans; Mwasa, Bridgit; Kimondo, Peter; Gardner, Emma; Von Dobschuetz, Sophie; Muriira, Joseph; Adul, Ben; Mwongela, Lawrence; et al. (Frontiers in Veterinary Science, 2022)
Background: Livestock farmers’ attitudes, practices, and behaviors are major factors in infection prevention and control of animal diseases. Kenya has the fourth largest global camel population, and the industry has grown over the last two decades, transforming beyond the traditional camel-keeping areas to include peri-urban camel trade and value chain growth. Camel is resilient, and it is a preferred species in the arid and semi-arid areas (ASALs) of Kenya. However, its management face myriads of challenges; to identify infection drivers and risky behaviors for camel respiratory illnesses and conditions in Kenya, we conducted a knowledge, attitudes, and practices (KAP) survey. Method: Using a set of tools (questionnaires, key informant interviews and focus group discussions), we interviewed camel owners, herders, agro-veterinary outlets, and other relevant value chain stakeholders in the two counties (n = 85). Data were analyzed using descriptive and analytic statistics. Results: Most camel owners/herders are male and a large population are relatively uneducated (85.5%). The camels were used primarily for milk and meat production, income generation and transport. Larger herd sizes (> 30 camels) and lack of formal education are risk factors for respiratory illnesses in camels. Major clinical signs and symptoms for respiratory conditions were coughing (85.7%), nasal discharge (59.7%), and fever (23.4%). Diseases, lack of feeds, theft, and marketing challenges are the major constraint to camel production in Kenya. Owners-herders use drugs indiscriminately and this may contribute to antimicrobial resistance challenges. Conclusion: Practitioners in the camel value chain want more commitment from the government and animal health officials on support services and access to veterinary services. Watering points, grazing areas, and marketing points are the primary areas for congregating camels and have a significant potential for disease spread. Kenya camels have a massive capacity for rural and ASALs’ livelihoods transformation but the identified health challenges, and other issues must be addressed. Further studies on the Kenyan camels’ respiratory microbial ecology is important to understand microbial risks and reduce the burden of zoonotic infections. Intensification of risk communication and community engagement, and messaging targeted at behavior change interventions should be directed at camel value chain actors.